Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Belanja Modal (Studi Kasus Pada Kabupaten/Kota di Provinsi Jawa Barat Tahun 2017-2019) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
This research aimed to examine the effect of economic growth (PE), localOwned Source Revenue (PAD), and General Allocation Fund (DAU) on the allocationof the capital Expenditures (BM) in the Regencies/Cities of West Java Province 2017-2019. The research was descriptive-quantitatif. While, the data were secondary whichtaken from the Directorate general of financial balance (DJPK) and the CentralStatistic Agency (BPS) West Java. The population in this study are regencies and citiesin West Java Province. The sample in this study is 27 (twenty seven) regions consistingof 18 (eighteen) Regencies and 9 (nine) Cities in West Java Province, so that the totaldata tested for 3 (three) years is 324 data. The analytical method used is multiple linearregression with Eviews version 9.0. The result showed that economic growth (PE) didnot positive and significant affect to capital expenditure in West Java Province 2017-2019. Local Revenue (PAD) and general allocation fund (DAU) had positive andsignificant effect to capital expenditure of regency/city in West Java province 2017-2019.